Traditional Criminal as a Form of Local Wisdom and Legal Reform in Indonesia - Engla Puspita Haria (IHSA Institute, 2021)
As one of the sovereign law countries, Indonesia has implemented a legal policy that has been rooted in and implemented since the Dutch colonial period. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the cu stomary system or customary criminal system is an embodiment and renewal of the criminal system and civil system, the concept of the customary law system itself focuses on the cultural values ??contained in the pattern of life of the Indonesian people, the importance of implementing the customary criminal system for the Indonesian government is an ideal of the nation which is reflected in the law and Pancasila as a guideline and identity of a nation, the customary law system itself is part of unwritten law and is seen as a companion law from criminal law and civil law as one of the laws that are authorized and carried out until the current government period.